2017
DOI: 10.1167/iovs.16-21321
|View full text |Cite|
|
Sign up to set email alerts
|

Biomechanical Responses of Lamina Cribrosa to Intraocular Pressure Change Assessed by Optical Coherence Tomography in Glaucoma Eyes

Abstract: PURPOSE. The purpose of this study was to measure change in anterior lamina cribrosa depth (ALD) globally and regionally in glaucoma eyes at different intraocular pressures (IOP).METHODS. Twenty-seven glaucoma patients were imaged before and after IOP-lowering procedures using optical coherence tomography. The anterior lamina was marked in approximately 25 locations in each of six radial scans to obtain global and regional estimates of ALD. ALD and its change with IOP were compared with optic disc damage, nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 74 publications
5
43
0
4
Order By: Relevance
“…This finding was supported in a subsequent study by Omodaka et al [53]. The disparity may be explained by the duration and severity of glaucoma, which could influence the compliance of the lamina in response to IOP changes [54]. Other studies have found no relationship between CCT and the LC [55,56].…”
Section: Biological Factorsmentioning
confidence: 74%
“…This finding was supported in a subsequent study by Omodaka et al [53]. The disparity may be explained by the duration and severity of glaucoma, which could influence the compliance of the lamina in response to IOP changes [54]. Other studies have found no relationship between CCT and the LC [55,56].…”
Section: Biological Factorsmentioning
confidence: 74%
“…15 Quantitative measurement of nerve fiber layer thickness and ONH structure with OCT 16 now permits detailed examination of LC substructure and its positional movements with change in IOP and intracranial pressure. [17][18][19][20] For digital analysis to be useful in clinical practice and research, automated methods are needed that require minimal observer input.…”
Section: Discussionmentioning
confidence: 99%
“…21 We previously showed that greater LC deformation with IOP change occurred in clock-hour regions in which there were more remaining nerve fibers. 18 Software to assess lamina change can and should provide regional data as illustrated here, to give a fuller picture of LC remodeling. It will be important to have both normative and glaucoma-specific databases of ALD to assess true abnormality and change.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although a causative link between high intraocular pressure and optic nerve damage is well-established in glaucoma, the exact mechanism remains only partially understood. 3 High IOP and IOP fluctuations cause biomechanical stress and strain that compress, dislocate, stretch and shear the LC.…”
Section: Introductionmentioning
confidence: 99%
“…4 This leads to a mechanical failure of the load-bearing connective tissues of the ONH, to damage of nearby axons and compromise of the optic nerve head (ONH) blood supply. 2,[4][5][6] The mechanical failure is followed by a posterior bowing and compaction of the LC. 4,7 Patient-specific properties of the LC may explain why some patients are more likely to develop glaucoma damage despite a similar IOP.…”
Section: Introductionmentioning
confidence: 99%